Modelling the environmental and terrestrial drivers of the spread of the invasive fall armyworm Spodoptera frugiperda in Africa - Adan, M.; Tonnang, H.; Greve, K.; Borgemeister, C.; Goergen, G. (2025)
The Fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) (Lep.: Noctuidae) a destructive invasive pest, poses a significant threat to maize cultivation in Africa, highlighting the need for a better understanding the factors affecting its prevalence. In this study we utilized the Maxent modelling approach to assess the impact of environmental and terrestrial parameters on the spread of FAW in Africa. We compared four different models based on their predictive accuracy: the most comprehensive model, which included bioclimatic factors, landscape structure, and FAW phenology, achieved an accuracy of 0.902. In contrast, models using only single categories of variables yielded lower accuracies, ranging from 0.760 to 0.844. Land use and land cover were identified as the primary contributors to FAW's habitat suitability, accounting for 53.6% of the influence. Precipitation patterns and elevation also played significant roles, contributing 12.4% and 8.2%, respectively. Additional analysis highlighted the importance of temperature, seasonality and precipitation during the driest month. These findings suggest, that both environmental, like climatic, and terrestrial, like land cover, factors are crucial for understanding the spread of FAW in Africa. These insights could lead to the development of more effective and better targeted FAW management strategies, that potentially would reduce the reliance on insecticide use.